Silk and insight a novel - Mishima, Yukio 1925-1970 (A Pacific Basin Institute book, 1998)
A novel on a strike at a silk plant in 1950s Japan, illustrating the true face of the much-touted Japanese paternalism. The company operated a network of spies and anyone falling ill was fired. The strike led to better working conditions throughout Japan.